CORRELATION BETWEEN INJURY OF IMPACT IN THE SHOULDER AND TIME OF PRACTICAL IN SWIMMING (Fiep Bulletin - online, 2014)
The objective of the present study was to correlate the practical time of swimming and the day of training with pain in the shoulder. The sample was composed for 15 swimmers, with age between 15 and 22 years (17,4; ±2,13), 10 of masculine sex and 5 of feminine of the clubs the Sport Club White Handle and CIEF, the two in Joao Pessoa - PB. The swimmers had answered to a composed questionnaire of 24 questions. The research demonstrated that all the evaluated ones had presented pain in the shoulder more than and a day of training of 04 hours per day, 13 interviewed had affirmed that they train the 04 years more than. The equation of correlation of the "r" of Pearson for the 0 variable was applied pain in the shoulder and practical pain and time in the shoulder and time of trainings, got following results - 0,19 and 0,22 respectively. The results of the research had taken the conclusion that stops this sample pain in the shoulder inversely is correlated with the time of practical of the sport and it is not correlated with the training day.
Keywords: Pain in the Shoulder; Training; Swimming